The Creep Test Study and Macro-Detail Analysis of Argillaceous Red Sandstone in Different Water-Containing States - Shuntao Guo; Shujie Wen; Hongyu Guo; Helin Fu (Advances in Civil Engineering)
In order to study the creep characteristics and failure mechanism of argillous red sandstone in a water-bearing state, uniaxial creep tests of argillous red sandstone under dry and saturated states are carried out under fractional loading. Burgers model is used to fit the test results and identify the parameters, and scanning electron microscopy is carried out on the cross section of the damaged sample. The mechanism of creep difference of argillaceous red sandstone with different water content is studied from the microscopic point of view. The results show that the uniaxial compressive strength of the saturated clay red sandstone is 46% of that of the dry clay red sandstone. The deformation level of the saturated clay red sandstone is lower than that of the dry clay red sandstone. The limit deformation of the creep failure of the water-bearing clay red sandstone is much smaller than that of the dry clay red sandstone. The long-term strength of the muddy red sandstone is 46.4 MPa in the dry state and only 14.1 MPa in the saturated state, as calculated at the steady-state creep rate. It is found that the Burgers model can describe the attenuation and stable creep of muddy red sandstone well. Through macro- and microanalysis, it is found that the compression failure form of argillaceous red sandstone belongs to x-shaped conjugate inclined plane shear failure. After saturation, the internal pores of argillaceous red sandstone become larger, and the cementation ability decreases, resulting in the decrease of rock sample strength.